Progress of Lead‐Free Halide Double Perovskites. Issue 12 (10th February 2019) - Igbari, Femi; Wang, Zhao‐Kui; Liao, Liang‐Sheng
Abstract: The field of halide metal perovskite photovoltaics has caught widespread interest in the last decade. This is seen in the rapid rise of power conversion efficiency, which is currently over 23%. It has also stimulated a widespread application of halide metal perovskites in other fields, such as light‐emitting diodes, field‐effect transistors, detectors, and lasers. Despite the fascinating characteristics of the halide metal perovskites, the presence of toxic lead (Pb) in their chemical composition is regarded as one of the major limiting factors preventing their commercialization. Addressing the toxicity issues in these compounds by a careful and strategic replacement of Pb 2+ with other nontoxic candidate elements represents a promising direction to fabricate lead‐free optoelectronic devices. Such attempts yield a halide double perovskite structure which allows flexibility for various compositional adjustments. Here, the authors present the current progress and setbacks in crystal structures, materials preparation, optoelectronic properties, stability, and photovoltaic applications of lead‐free halide double perovskite compounds. Prospective research directions to improve the optoelectronic properties of existing materials are given that may help in the discovery of new lead‐free halide double perovskites. Abstract : Halide double perovskites represent a promising direction to fabricate lead‐free optoelectronic devices. The current progress and setbacks in crystal structures, materials preparation, optoelectronic properties, stability, challenge, and photovoltaic applications of lead‐free halide double perovskite compounds are reviewed in detail.